Laboratory diagnosis of megaloblastic anaemia: current methods assessed by external quality assurance trials. Issue 4 (April 1987) - Dawson, D W; Fish, D I; Frew, I D; Roome, T; Tilston, I
Abstract : The results of an Interregional quality assurance scheme for tests in the diagnosis of megaloblastic anaemia were reviewed to assess the methods used. Serum folate assays showed great variation between methods, partly due to limitations in assessment by external quality assurance. Red cell folate assays yielded widely different results and much imprecision due both to the differences in preparation of the haemolysate and to the problems inherent in radioassay of a mixture of folate compounds. Intrinsic factor antibody tests showed appreciable variation in sensitivity. There was considerable inconsistency in the detection of polymorph nuclear hypersegmentation.